Effect of Alkaline Treatment on Tensile Properties of HybridComposite of Arachis hypogaea and Pentaclethra macrophyllaAgro-Waste Fibres - Ekene, Ilechukwu Anthonia; Okechukwu, Chikelu Peter; Amaechi, Okafor Anthony; Ezechi, Dara Jude; Princewill, Odeh Calistus (Institut Teknologi Pendidikan Indonesia, 2025)
Recently, there has been a growing interest in using natural fibres for developing sustainable composites, mainly because synthetic fibres can harm the environment. However, one of the challenges is that these natural fibres often don’t bond well with the matrices, which limits their use. This is why research aimed at improving the properties of these composites is so important, and one effective method is alkaline treatment. In this study, agro-waste fibres from the fruit husks of Arachis hypogaea and Pentaclethra macrophylla were processed by treating them with NaOH solutions at concentrations of 2%, 4%, 6%, 8%, and 10% by weight. The tensile properties of the hybrid composites made from these fibres were then assessed using analysis of variance and regression analysis in Minitab software. The results showed that the composite made with the 2% NaOH-treated fibres had the highest tensile strength and elastic modulus. Interestingly, beyond the 2% NaOH treatment, both tensile strength and elastic modulus started to decline. Overall, we observed increases of 3% in tensile strength and 6% in elastic modulus. Additionally, the ANOVA and regression analysis yielded a P-value of ≤0.05 in both cases, indicating that the treatment significantly impacts the hybrid composite's tensile strength and elastic modulus. Therefore, our findings suggest that treating fibres with NaOH is a promising way to enhance the mechanical properties of hybrid fibre composites.